NBA-Drafted vs. non-drafted basketball players: A comparative analysis of neuromuscular performance characteristics - Cabarkapa, D.; Cabarkapa, D. V.; Comfort, P.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2026)
The purpose of this investigation was to examine differences in lower-body neuromuscular performance characteristics between National Basketball Association (NBA)-drafted and non-drafted professional male basketball players. Eighty-six athletes volunteered to participate in this study, from which 10 were NBA first or second round draft picks, and the remaining 76 were nondrafted athletes playing at various professional basketball leagues across Europe. Each athlete performed 2 countermovement vertical jumps (CMJs) with no arm swing while standing on a dual uniaxial force plate system sampling at 1,000 Hz. Twenty-four force-time metrics were included in the analysis, within both braking (i.e., eccentric) and propulsive (i.e., concentric) phases of the CMJ. Independent-sample t -tests were used to determine statistically significant between-group differences ( p < 0.05), whereas Cohen's d was used to determine difference magnitudes. Overall, the findings indicate that NBA-drafted athletes displayed considerably greater force and power-producing capabilities when compared with their non-drafted counterparts, when expressed in absolute terms, such as mean braking force (1,016.4 ± 79.6 vs. 913.8 ± 93.1 N), peak braking power (2,151.7 ± 576.1 vs. 1,709.9 ± 525.9 W), mean propulsive force (2,183.2 ± 275.7 vs. 1,977.3 ± 215.5 N), and peak propulsive power (5,719.3 ± 699.3 vs. 5,139.9 ± 607.2 W). However, when expressed relative to body mass, no differences were observed in any of the aforementioned metrics, with no difference in jump height (37.3 ± 5.3 vs. 37.2 ± 4.8 cm) and reactive strength index-modified (0.554 ± 0.078 vs. 0.536 ± 0.099). In addition, time-to-takeoff, countermovement depth, and braking and propulsive phase durations were all similar in magnitude between the groups ( d = 0.019-0.148), suggesting that both used similar jump strategies.